Russian-Indonesian Relations in the 21 Century - L. M. Efimova (Vestnik MGIMO-Universiteta)
In XXI century a new faze has begun in Russian-lndonesian relations which are based on pragmatism and supremacy of nations interests of both sides. Cooperation in the political, military, trade, investment, social and cultural spheres is strengthening, cooperation on international and regional arenas is widening. In relations with Indonesia, as well as with other Southeast Asian states Russia's main purpose is stability based on the principles of equality, mutual respect and benefit according to the international law. Indonesia's foreign policy maintains its free and active character. Russian-lndonesian relations in the 21 century are marked with intensive political dialogue. Political ties are developing steadily. Mutual presidential visits has become regular. Close cooperation has been established between state institutions on various levels. The most successful cooperation is developing in scientific, technological and military spheres. Thie cooperation is especially important for Indonesia in order to diminish its dependence on the West in these aspects. Relations in trade and economic spheres are not very intensive, but are stable and have a positive dynamics. Indonesia was always a good trade partner for Russia. Direct business con tacts are now developing between the two countries and this fact in very significant for the future economic cooperation. Nowadays Russian regions have begun to establish direct ties with Indonesian regions. Humanitarian sphere constitute an important aspect of Russian-lndonesian relations. Cooperation in education is going on successfully. A new phenomenon represents friendly contacts between religious leaders of both countries. In general mutually beneficial and fruitful cooperation between Russia and Indonesia is steadily progressing and opening brilliant perspectives.